2016
DOI: 10.1089/neu.2014.3855
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapies for Traumatic Brain Injury: Retrospective Considerations

Abstract: Patients enrolled in clinical trials for traumatic brain injury (TBI) may present with heterogeneous features over a range of injury severity, such as diffuse axonal injury, ischemia, edema, hemorrhage, oxidative damage, mitochondrial and metabolic dysfunction, excitotoxicity, inflammation, and other pathophysiological processes. To determine whether combination therapies might be more effective than monotherapy at attenuating moderate TBI or promoting recovery, the National Institutes of Health funded six pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 112 publications
(149 reference statements)
0
43
0
Order By: Relevance
“…[63][64][65][66] Indeed, the recent review from the RFA described earlier reported that one study demonstrated worse results with the combination therapy relative to the monotherapy. 46 In addition, EE alone rendered substantial therapeutic benefit to functional outcomes, suggesting that identification of specific complementary pharmacotherapies, or quantification of more appropriate dosages, may help to maximize the therapeutic effect of this paradigm. For example, the real-world applicability of the continuous EE paradigm (i.e., 24 h per day) is limited, because even inpatients do not receive around-the-clock rehabilitation services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65][66] Indeed, the recent review from the RFA described earlier reported that one study demonstrated worse results with the combination therapy relative to the monotherapy. 46 In addition, EE alone rendered substantial therapeutic benefit to functional outcomes, suggesting that identification of specific complementary pharmacotherapies, or quantification of more appropriate dosages, may help to maximize the therapeutic effect of this paradigm. For example, the real-world applicability of the continuous EE paradigm (i.e., 24 h per day) is limited, because even inpatients do not receive around-the-clock rehabilitation services.…”
Section: Resultsmentioning
confidence: 99%
“…46 Although the authors discussed numerous relevant limitations for the lack of efficacy, a salient plausible explanation for the lack of added or synergistic effects may be that in all of the studies involved with the RFA, the potential benefit of rehabilitation itself was omitted. 46 Hence, the present behavioral study was designed to investigate whether the combined therapeutic potential of EE, a pre-clinical model of neurorehabilitation, 18,[47][48][49] and chronic administration of MPH would be greater than that of either treatment alone on recovery of motor and cognitive function. The beam balance and beam walk data revealed that both the MPH and VEH groups assigned to EE displayed improved performance relative to the STD-housed groups regardless of whether receiving MPH or VEH.…”
Section: Discussionmentioning
confidence: 99%
“…One particular problem with drugs that failed clinical trials is that they were too specific in their treatment targets. This has resulted in a large push in recent years to assess combination therapies, targeting multiple mechanisms of action [121]. As nutritionally-based therapies supplement basic biological function and have therapeutic action in the injured brain, these therapies may eventually represent an important component of combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Our group is investigating the use of NAC in combination with probenecid, the prototypical organic anion transporter inhibitor, in the treatment of pediatric traumatic brain injury (Margulies et al, 2016). We proposed that a potentially synergistic interaction between NAC and probenecid exists to enhance antioxidant capacity of the brain after injury.…”
Section: Introductionmentioning
confidence: 99%